Comparing awareness of mental health issues and cognitive behavioural therapy in male and female UK Premier League academy soccer players and university students - Beukes, E.; Wilkins, L.; Zaborski, Z.; Allen, P. (Journal of Sport and Human Performance, 2019)
The aim of this study was to obtain information regarding elite soccer academy players` and university students` awareness of common mental disorders and intervention options. A cross-sectional design compared perceptions of male and female Premier League soccer academy players with those of male and female university students using a custom-made questionnaire. The prevalence of experiences of anxiety and depression was high in all groups. Significantly less male soccer players had heard of cognitive behavioural therapy (CBT) or knew what CBT was compared with all other groups. Barriers to obtaining support for mental health concerns included not knowing how or when to seek help and what treatment entailed. Participants indicated that they would first turn to family and friends rather than coaches or professionals for help. A preference for CBT over counselling was indicated by the majority of the soccer players and students. The findings of this study can be applied during the development of suitable evidence-based interventions tailored for elite academy soccer players.